Comparative evaluation of Bailey manoeuvre of deep extubation with conventional awake extubation technique - A randomized clinical study - Rahul Tiwari,; Suman Gupta,; Youvaraj M, (Asian Journal of Medical Sciences, 2024)
Background: Extubation is a critical procedure in anesthesia and critical care, often accompanied by complications, such as bucking, coughing, and hemodynamic instability, particularly after major surgeries. The Bailey manoeuvre, involving deep extubation with the i-gel laryngeal mask airway (LMA), may mitigate these issues. The study was planned to compare the hemodynamic effects and side effect profiles of conventional awake endotracheal extubation and exchange extubation with the i-gel LMA. Aims and Objectives: The study was designed to compare hemodynamic stress response and respiratory complication between the conventional extubation group and the following exchange extubation group. Materials and Methods: In a prospective, randomized, single-blinded controlled study, 60 patients undergoing surgery under general anesthesia were divided into two groups: Group T (awake extubation) and Group L (exchange extubation with the i-gel LMA). Hemodynamic parameters and side effects were recorded and analyzed. Results: Group L exhibited significantly lower heart rates, systolic and diastolic blood pressures, and mean arterial pressures at various time points post-extubation compared to Group T. The incidence of hypertension was significantly higher in Group T (90%) versus Group L (50%). Bucking and coughing less in the i-gel LMA exchange group compared to the standard endotracheal tube extubation group. Conclusion: Exchange extubation with the i-gel LMA offers better hemodynamic stability and a lower incidence of hypertension compared to conventional awake extubation. This technique may be particularly beneficial for high-risk patients and those undergoing complex surgeries.